An Analysis of Feminism in Brave Movie: A Perspective on Gender Construction and Woman's Independence - Sari, Nur Ramidah; Adam, Adam; Dewi, Desi Surlitasari (Journal of Language and Literature Studies, 2026)
This study analyzes the representation of gender constructs and female independence in the film Brave (2012) from a feminist perspective. This Pixar film is important to study because it presents a narrative that differs from traditional Disney princess films, in which female characters tend to be portrayed as passive, waiting to be rescued, and their happiness dependent on male characters. Brave, on the other hand, presents female characters who actively determine their own destinies, making it an interesting case for feminist analysis in children's animated films. The research uses a descriptive qualitative method with documentation techniques through observation of scenes and dialogues relevant to gender issues. The data is analyzed through the stages of identification, thematic classification, and interpretation using bell hooks' (2000) feminist theoretical framework, particularly the concept of feminism as a transformative movement and the importance of solidarity between generations of women.. The results of the study show three main findings. First, the film depicts a rejection of traditional gender constructs through Merida's refusal to be married off and her claim to the right to determine her own destiny. Second, female independence is represented as the ability to make decisions and take responsibility, rather than dependence on men. Third, the mother-daughter relationship becomes a space for negotiating gender values between generations. The film emphasizes that women's independence can be achieved through dialogue and relationship transformation, not isolation from the family. These findings have important implications for media representation and gender equality, showing that animated children's films can be a medium for spreading accessible feminist values and influencing the way children, especially girls, understand gender roles and develop expectations about women's independence from an early age. Brave offers a more inclusive feminist perspective in the discourse on gender in popular media.